2019
DOI: 10.1002/ese3.313
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between the influencing factors and the multiple responses of coal‐like materials using Taguchi‐Gray correlation analysis for their utilization in gas seepage studies

Abstract: Coal‐like sampling obtained through compression molding is an important application of powder compression molding technology in mining engineering. To obtain ideal coal‐like samples for the revelation of the seepage property of low‐permeability soft coals, gas seepage studies, which utilized the Taguchi method, were performed on coal‐like materials with different particle sizes, activated carbon weight, Portland cement weight, and forming pressure. The effect of a single factor on the fluid‐solid coupling prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The water storage capacity depends on the porosity of the coal specimens, while water adsorption is an external manifestation of the size and distribution of cracks in the coal, and micro‐pore structure also has a certain effect on seepage and water drive . An increase in the water adsorption of coal specimens indicates an increase and extension of cracks within the structure and an increase in fluid permeability in the coal . The curve of water adsorption under cyclic wetting‐drying is shown in Figure .…”
Section: Results and Analysismentioning
confidence: 99%
“…The water storage capacity depends on the porosity of the coal specimens, while water adsorption is an external manifestation of the size and distribution of cracks in the coal, and micro‐pore structure also has a certain effect on seepage and water drive . An increase in the water adsorption of coal specimens indicates an increase and extension of cracks within the structure and an increase in fluid permeability in the coal . The curve of water adsorption under cyclic wetting‐drying is shown in Figure .…”
Section: Results and Analysismentioning
confidence: 99%
“…Gypsum (main ingredients: gypsum, sand, calcium carbonate, and additives), cement (32.5# ordinary Portland pozzolana cement), pulverized coal (lignite from the Dongsheng Coalmine, China), and sand were selected as similar materials to make coal-like samples (Figure ). , The testing results of the proximate analysis, mechanics, and porosity of lignite are presented in Table . Based on a pilot experiment in the laboratory, we concluded that the mechanical properties of the coal-like samples were similar to those of low-rank coal when the weight ratio of pulverized coal (0–1 mm):cement:gypsum:sand (0.25–0.5 mm):water was 1:3:1:1:2 (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…It was also found that the coal particle sizes had a significant effect on the strength and permeability of the coal-like briquettes. Zhong et al found that the compressive strength and Young’s modulus of German brown coal particles significantly increased as the specimen size (diameter range of 0.8–6.3 mm) decreased. Dong et al concluded that the effective elastic moduli and tensile strengths were related to tectonic coal particles (size range of 0.2–4.0 mm) as a power function.…”
Section: Introductionmentioning
confidence: 99%
“…Although the method will improve the prediction accuracy, the time cost will be relatively high. At present, the most common feature selection method applied in industrial production processes is the filter methods, such as correlation-based analysis methods [6]- [8]; wrapper methods, such as variable pruning methods [9], [10], genetic algorithm-based methods [11].…”
Section: A Feature Extractionmentioning
confidence: 99%